The Effectiveness of Wordwall Media in Developing Arabic Vocabulary Skills in Grade X Students at MA Al-Falah, East Jakarta - Al-Azamat Khan, Nawwal Fariha; Azmy Ali Muchtar (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Vocabulary is a fundamental element in Arabic language learning, as students cannot master the four language skills without a sufficient vocabulary base. With the development of technology, digital educational tools like Wordwall offer interactive and engaging methods to support vocabulary acquisition. This study investigates the effectiveness of Wordwall media in enhancing Arabic vocabulary mastery among tenth-grade students at Al-Falah Islamic Senior High School, East Jakarta. Using a quantitative approach with a quasi-experimental design (pretest-posttest) involving one group of 15 students, data were collected through vocabulary tests administered before and after using Wordwall. The results showed an increase in the average score from 78.00 (pretest) to 97.66 (posttest). A paired t-test revealed a significant difference (t = -7.554, p < 0.001), indicating the positive impact of Wordwall on vocabulary mastery. The study concludes that Wordwall is an effective tool for improving students’ Arabic vocabulary and recommends its integration into Arabic language teaching programs. It also encourages the use of other innovative media to enhance language learning in the digital era. Keywords: Wordwall, vocabulary, effectiveness, Arabic language education